Nickel ferrite: synthesis and application for voltammetric determination of uric acid - Nguyen Thi Vuong Hoan (TGC); Nguyen Ngoc Minh; Nguyen Thi Lieu; Nguyen Van Thang; Vo Thang Nguyen; Nguyen Thi Thanh Tu; Tran Thanh Tam Toan; Nguyen Hoang Tuan; Duong Quang Nhan; Ho Van Minh Hai; Tran Ngoc Tuyen; Dinh Quang Khieu (My University, 2021)
Nickel ferrite: synthesis and application for voltammetric determination of uric acid
Keywords: Nickel ferrite